New Ideas in Assessing and Encouraging Students of an Educational Institution Before Schools - Sobirova Gulnozakhon Lochinbek Qizi (Global Scientific Publishing, 2022)
This article presents effective ways to motivate students, technologies for using these methods. The article also provides comprehensive information on why incentives are needed. Taking a lesson in a situation using these effective methods will help to educate the next generation in the spirit of healthy competition
Keywords: stimulation, stimulation, traffic light, green, red, yellow